2017
DOI: 10.1111/bjhp.12254
|View full text |Cite
|
Sign up to set email alerts
|

Explaining infant feeding: The role of previous personal and vicarious experience on attitudes, subjective norms, self‐efficacy, and breastfeeding outcomes

Abstract: ObjectivesBreastfeeding confers important health benefits to both infants and their mothers, but rates are low in the United Kingdom and other developed countries despite widespread promotion. This study examined the relationships between personal and vicarious experience of infant feeding, self‐efficacy, the theory of planned behaviour variables of attitudes and subjective norm, and the likelihood of breastfeeding at 6–8 weeks post‐natally.DesignA prospective questionnaire study of both first‐time mothers (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
80
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 39 publications
3
80
1
3
Order By: Relevance
“…The mean scores of self-efficacy for breastfeeding was higher and statistically significant for the IG (p<0.001) from the 2 nd week postpartum, and this difference remained until the 8 th week postpartum. The relationship between EBF and high scores of maternal self-efficacy for breastfeeding is well documented in studies that analyzed this variable (8,10) . The study investigating the role of psychosocial factors in EBF up to children's 6 months of life demonstrated that self-efficacy for breastfeeding is a strong predictor for both the intent and duration of breastfeeding (4) .…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The mean scores of self-efficacy for breastfeeding was higher and statistically significant for the IG (p<0.001) from the 2 nd week postpartum, and this difference remained until the 8 th week postpartum. The relationship between EBF and high scores of maternal self-efficacy for breastfeeding is well documented in studies that analyzed this variable (8,10) . The study investigating the role of psychosocial factors in EBF up to children's 6 months of life demonstrated that self-efficacy for breastfeeding is a strong predictor for both the intent and duration of breastfeeding (4) .…”
Section: Discussionmentioning
confidence: 96%
“…However, studies indicate that maternal age has not always posed as a risk factor for early weaning (9,18) . Previous experience in breastfeeding is one of the sources of development of beliefs in maternal self-efficacy in breastfeeding (7) and an important factor for the practice of EBF (4,8) . This experiment was similar in both groups and supported the results of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations